The Influence Of Drill Training Method On Basic Futsal Playing Skills In U-15 Men's Players At Surakarta Futsal Academy - Dedy Prasetyo Pamungkas; Bambang Wijanarko; Manshuralhudlori (Java Mutiara Media, 2024)
This study aims to determine the effect of drill training methods on basic futsal playing skills in U-15 male players of the Surakarta Futsal Academy. This research is a research that uses an experimental method with One Group Pretest-Posttest Design research design. The subjects in this study were all 26 U-15 male players of the Surakarta Futsal Academy. This study used an experimental design in one group using the drill training method treatment. This study was conducted as many as 16 meetings with a frequency of meetings 3 times in 1 week. Pretest and posttest data collection using basic futsal playing skills tests. The data analysis technique used is the normality test using the Shapiro Wilk test while the hypothesis test uses the paired sample t test using the help of the SPSS program.. The results of data analysis with paired sample t test showed that the value of Sig. (2 Tailed) was 0.000 < 0.05 which means that there is a significant influence between drill training methods on basic futsal playing skills in U-15 boys of Surakarta Futsal Academy. The average pretest result was 69.2888 while the average in the posttest was 59.8569. The results of the average pretest and posttest showed that there was an increase of 13.62%. This shows that there is an improvement in basic futsal playing skills after treatment using the drill training method. Based on the results of research and analysis of research data, it can be concluded that there is a significant influence between drill training methods on basic futsal playing skills in U-15 male players of the Surakarta Futsal Academy.